2020
DOI: 10.1002/fsn3.1630
|View full text |Cite
|
Sign up to set email alerts
|

Developmental assessments during the first 5 years of life in infants fed breast milk, cow's milk formula, or soy formula

Abstract: Objective To investigate the effects of infant feeding mode on childhood cognition and language as the differential effects of infant feeding on development remain understudied. Methods Breastfed [BF, 174], cow's milk‐based formula‐fed [MF, 169], or soy protein‐based formula‐fed [SF, 161] children were longitudinally tested from age 3 to 60 months for neurodevelopment. Data were analyzed using mixed models while adjusting for multiple covariates. Sex differences were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(32 reference statements)
0
9
2
Order By: Relevance
“…For the rest of the motor skills analyzed, there were no statistically significant differences found. These results are distinct from those of Bellando et al (2020) and Michels et al (2017), who did not find any effect of feeding type on motor skills beyond the 3 first months of life. Our results are along the lines of those of Jardí et al (2018) and Kádár et al (2021) since we found that the influence of infant feeding type on motor skills continue for longer periods of time.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For the rest of the motor skills analyzed, there were no statistically significant differences found. These results are distinct from those of Bellando et al (2020) and Michels et al (2017), who did not find any effect of feeding type on motor skills beyond the 3 first months of life. Our results are along the lines of those of Jardí et al (2018) and Kádár et al (2021) since we found that the influence of infant feeding type on motor skills continue for longer periods of time.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, studies analyzing the effects beyond 3 years are even more few. Bellando et al (2020) found that, at the age of 3 months, breastfed infants displayed better motor development than formula-fed infants. However, at 12 and 24 months, no differences were found between both groups.…”
Section: Feeding Typementioning
confidence: 92%
“…By contrast, our data suggested an almost equal effect of total months of breastfeeding compared to formula/mixed with breastfeeding on both tHcy-and B12 levels in a dose-responsive way. Feeding practices were not directly associated with psychomotor test results, as opposed to findings in other studies 31,32 showing breastfeeding to be associated with better outcome in psychomotor tests. As our study was not designed for this outcome our inconsistent findings should be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 99%
“…In infancy, the intestinal bacterial colonization of the newborn will determine whether the baby can maintain their health while growing up. Compared with infant formula and soybean milk, breastfed infants have better neurodevelopment characteristics, motor development, and language development [ 67 ]. The colonization of intestinal flora in breastfed infants is significantly different from that in formula-fed infants [ 68 ].…”
Section: Effect Of Endotoxin On Infantsmentioning
confidence: 99%